DMLC tracking and gating can improve dose coverage for prostate VMAT. Issue 9 (14th August 2014) - Colvill, E.; Poulsen, P. R.; Booth, J. T.; O'Brien, R. T.; Ng, J. A.; Keall, P. J.
Abstract : Purpose: : To assess and compare the dosimetric impact of dynamic multileaf collimator (DMLC) tracking and gating as motion correction strategies to account for intrafraction motion during conventionally fractionated prostate radiotherapy. Methods: : A dose reconstruction method was used to retrospectively assess the dose distributions delivered without motion correction during volumetric modulated arc therapy fractions for 20 fractions of five prostate cancer patients who received conventionally fractionated radiotherapy. These delivered dose distributions were compared with the dose distributions which would have been delivered had DMLC tracking or gating motion correction strategies been implemented. The delivered dose distributions were constructed by incorporating the observed prostate motion with the patientˈs original treatment plan to simulate the treatment delivery. The DMLC tracking dose distributions were constructed using the same dose reconstruction method with the addition of MLC positions from Linac log files obtained during DMLC tracking simulations with the observed prostate motions input to the DMLC tracking software. The gating dose distributions were constructed by altering the prostate motion to simulate the application of a gating threshold of 3 mm for 5 s. Results: : The delivered dose distributions showed that dosimetric effects of intrafraction prostate motion could be substantial for some fractions, with an estimated dose decrease of more than 19% and 34% from the planned CTV D 99% and PTV D 95% values, respectively, for one fraction. Evaluation of dose distributions for DMLC tracking and gating deliveries showed that both interventions were effective in improving the CTV D 99% for all of the selected fractions to within 4% of planned value for all fractions. For the delivered dose distributions the difference in rectum V 65% for the individual fractions from planned ranged from −44% to 101% and for the bladder V 65% the range was −61% to 26% from planned. The application of tracking decreased the maximum rectum and bladder V 65% difference to 6% and 4%, respectively. Conclusions: : For the first time, the dosimetric impact of DMLC tracking and gating to account for intrafraction motion during prostate radiotherapy has been assessed and compared with no motion correction. Without motion correction intrafraction prostate motion can result in a significant decrease in target dose coverage for a small number of individual fractions. This is unlikely to effect the overall treatment for most patients undergoing conventionally fractionated treatments. Both DMLC tracking and gating demonstrate dose distributions for all assessed fractions that are robust to intrafraction motion.